Nouvelles migrations sud-américaines au Chili : Rapports de sexe, classe, et « race » en santé - Nanette Liberona (Les Cahiers ALHIM)
The arrival of new South-American users of the public health system in Chile has created new inter-ethnic relationships between agents, administrative staff and professionals of the health system and the patients. Likewise it has created new inter-ethnic relationships between nationals and foreigners. As consequence this provokes inequalities, discrimination and bad treatments towards the latter. This article intent to show the roles of social relationships in terms of sex, class and race in different forms of discriminatory treatment towards the otherness. It also highlights, through the discourse of the dominants, the legitimacy of practices that let to class and sexist stigma and racial, ethnic and sexist domination. The articulation of these social relationships provides grounds to explain that the exercise of power of these agents obstacle the access to care to the immigrants, affecting their rights to health and causing a negative impact to their physical and mental health.